White Diaspora : The Suburb and the Twentieth-Century American Novel - Jurca, Catherine (Book collections on Project MUSE., 2011)
This is the first book to analyze our suburban literary tradition. Tracing the suburb's emergence as a crucial setting and subject of the twentieth-century American novel, Catherine Jurca identifies a decidedly masculine obsession with the suburban home and a preoccupation with its alternative--the experience of spiritual and emotional dislocation that she terms "homelessness." In the process, she challenges representations of white suburbia as prostrated by its own privileges. In novels as disparate as Tarzan (written by Tarzana, California, real-estate developer Edgar Rice Burroughs), Richar